ChemInform Abstract: A Scalable Synthesis of (R, R)‐2, 6‐Dimethyldihydro‐2H‐pyran‐4(3H)‐one. Issue 8 (February 2016) - Young, Ian S.; Haley, Matthew W.; Tam, Annie; Tymonko, Steven A.; Xu, Zhongmin; Hanson, Ronald L.; Goswami, Animesh
Abstract: Key step of the improved synthesis of title compound (VIII) is the Kulinkovich cyclopropanation, and subsequent oxidative fragmentation of the cyclopropanol (IV).